2015
DOI: 10.3390/w7073861
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Water Quality between the Runoff Entrance and Middle of Recycling Irrigation Reservoirs

Abstract: Recycling irrigation reservoirs (RIRs) are an emerging aquatic ecosystem of critical importance, for conserving and protecting increasingly scarce water resources. Here, we compare water quality between runoff entrance and middle of four RIRs in nurseries in Virginia (VA) and Maryland (MD). Surface water temperature (T) and oxidation-reduction potential (ORP) were lower in the middle than at the entrance, while the trend was opposite for dissolved oxygen (DO), pH and chlorophyll a (Chla). The magnitude of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Zhang et al (2015bZhang et al ( , 2016 showed annual seasonal vertical variations in water quality of some of these same RCBs, stratification being the most prominent event. However, the importance of which variable contributes to water quality variation differs per season and per waterway (Ouyang et al, 2006;Piñol et al, 1992;Zhang et al, 2015bZhang et al, , 2016. In addition, seasonal differences between spring and summer would be confounded by fertilizer practices (fertilizer type, time of application, and rate) and the effect of temperature and rainfall on release rates of CRFs.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Zhang et al (2015bZhang et al ( , 2016 showed annual seasonal vertical variations in water quality of some of these same RCBs, stratification being the most prominent event. However, the importance of which variable contributes to water quality variation differs per season and per waterway (Ouyang et al, 2006;Piñol et al, 1992;Zhang et al, 2015bZhang et al, , 2016. In addition, seasonal differences between spring and summer would be confounded by fertilizer practices (fertilizer type, time of application, and rate) and the effect of temperature and rainfall on release rates of CRFs.…”
Section: Discussionmentioning
confidence: 96%
“…The stream (VA10) is a local natural water source that does not receive runoff from the nursery, thus used as a comparison with VA11, VA12, and VA13. Descriptions of MD and VA RCBs and stream have been previously published using the same label designation (Zhang et al, 2015a(Zhang et al, , 2015b(Zhang et al, , 2016. A description of MS11 was previously described in Copes et al (2015) where it was labeled M2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal efficacy for nitrogen in FTWs ranges from 25 to 89%, while phosphorus removal efficacy ranges from 4 to 79% (Lynch et al 2015 ; White and Cousins 2013 ; Zhang et al 2015 ). Plant uptake of nutrients is a pertinent mechanism driving nutrient remediation within FTWs.…”
Section: Remediation Technologiesmentioning
confidence: 99%
“…Ornamental and vegetable plant production operations may have several sources of water, such as open waterways (e.g., streams, rivers, and lakes) and subterranean water sources (e.g., aquifers and wells), that are used for irrigation. The homogeneity or heterogeneity of water quality from open waterways, including RCBs, results from the physical dynamics of the water body that influences the extent of mixing or layering of water (Chiandet and Xenopoulos, 2016;Song et al, 2013;Zhang et al, 2015aZhang et al, , 2015bZhang et al, , 2016. The consideration of withdrawing water from an RCB for plant irrigation requires knowing the range of water properties within the water body, so levels can be predictably managed to produce quality plant material for commercial sales.…”
mentioning
confidence: 99%